2004
DOI: 10.1111/j.1468-3148.2004.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Competence in Persons with Prader‐Willi, Williams and Down's Syndromes

Abstract: Background  This study explores everyday social competence in the lives of persons with three genetic intellectual disability syndromes. Methods  Using parent reports on the Social and Activity Competence domains of Achenbach's Child Behavior Checklist (CBCL), socially competent behaviours were examined in 58 persons with Williams syndrome, 54 persons with Prader‐Willi syndrome, and 65 persons with Down's syndrome. Results  The Down's syndrome group showed the highest overall social competence scores, while in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 31 publications
1
76
0
3
Order By: Relevance
“…Parents of people with PWS are also less likely to report musical activities, when freely listing "non-sport activities" that their children enjoy, than are parents of people with Williams or Down syndromes (Rosner, Hodapp, Fidler, Sagun, & Dykens, 2004). It is unclear, however, whether reduced parental reporting of active musical activities reflects a general lack of interest in music or a more specifically altered psychology of music in PWS.…”
Section: Genomic Imprinting Is Implicated In the Psychology Of Musicmentioning
confidence: 82%
“…Parents of people with PWS are also less likely to report musical activities, when freely listing "non-sport activities" that their children enjoy, than are parents of people with Williams or Down syndromes (Rosner, Hodapp, Fidler, Sagun, & Dykens, 2004). It is unclear, however, whether reduced parental reporting of active musical activities reflects a general lack of interest in music or a more specifically altered psychology of music in PWS.…”
Section: Genomic Imprinting Is Implicated In the Psychology Of Musicmentioning
confidence: 82%
“…In particular, Hodapp and Burack (2006) describe that children may choose to engage in activities that involve areas of relative strength, and as such, they may practice those skills more intensely than areas of weakness. Indeed, Rosner, Hodapp, Fidler, Sagun, and Dykens (2004) found differences in patterns of participation in various activities and sports. From a dynamic systems perspective, these patterns of strength and weakness are attractor states that become stronger over time, as they are practiced.…”
Section: Strong Versus Weak Attractors In Neurogenetic Disordersmentioning
confidence: 97%
“…In terms of profiles, why do strengths become relatively stronger and weaknesses relatively weaker? In one study, Rosner et al [2004] found that, compared to those with either Down syndrome or Prader-Willi syndrome, fewer children with Williams syndrome routinely engaged in drawing, puzzles, arts and crafts, and other visually based leisure time activities. But, in addition to avoiding etiology-related weaknesses, do children with any of these syndromes capitalize on their strengths?…”
Section: Need To Appreciate That Behavior Changes Over Timementioning
confidence: 97%